In vivo and in vitro identification of Z-BOX C – a new bilirubin oxidation end product. Issue 19 (13th March 2018) - Ritter, Marcel; Neupane, Sandesh; Seidel, Raphael A.; Steinbeck, Christoph; Pohnert, Georg
Abstract : A new bilirubin degradation end product was isolated and characterized. Abstract : A new bilirubin oxidation end product (BOX) was isolated and characterized. The formation of the so-called Z -BOX C proceeds from bilirubin via propentdyopents as intermediates. This BOX was detected in pathological human bile samples using liquid chromatography/mass spectrometry and has potential relevance for liver dysfunction and cerebral vasospasms.